2014
DOI: 10.1177/1088868314530516
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adult Attachment Styles in American College Students Over Time

Abstract: The current article examines changes over time in a commonly used measure of adult attachment style. A cross-temporal meta-analysis was conducted on 94 samples of American college students (total N = 25,243, between 1988 and 2011) who chose the most representative description of four possible attachment styles (Secure, Dismissing, Preoccupied, and Fearful) on the Relationship Questionnaire. The percentage of students with Secure attachment styles has decreased in recent years (1988: 48.98%; 2011: 41.62%), wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 193 publications
4
91
1
3
Order By: Relevance
“…When people lack the inspiration of an ideal self and place less value on opportunities for advancement, they may extract fewer benefits from their experiences in relationships, occupation, and recreational activities, and experience lower psychological well-being as a result. Recent research indicates that there the number of securely attached individuals may be decreasing (Konrath et al, 2014), a concerning finding given the results of the current studies, which would suggest that a decrease in secure attachment would be associated with a decrease in adaptive regulatory style.…”
Section: Theoretical Implicationsmentioning
confidence: 63%
See 1 more Smart Citation
“…When people lack the inspiration of an ideal self and place less value on opportunities for advancement, they may extract fewer benefits from their experiences in relationships, occupation, and recreational activities, and experience lower psychological well-being as a result. Recent research indicates that there the number of securely attached individuals may be decreasing (Konrath et al, 2014), a concerning finding given the results of the current studies, which would suggest that a decrease in secure attachment would be associated with a decrease in adaptive regulatory style.…”
Section: Theoretical Implicationsmentioning
confidence: 63%
“…While sex showed almost no associations with the relevant constructs (except fearful attachment, r = −.13, p b .05), age was positively related to several constructs, most notably both ideal (r = .16, p b .05) and ought discrepancies (r = .15, p b .05). Nevertheless, previous research has implicated both age (Konrath, Chopik, Hsing, & O'Brien, 2014) and sex (Bartholomew & Horowitz, 1991) as potential moderators of attachment style, and so their main effects and all possible interactions were included in regression models.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Turkish participants reported more anxious regulation strategies, which is consistent with the collectivistic values of Turkish culture, such as preoccupation with relationships, reassurance of others, and interdependency (Citlak et al, 2008 Sümer & Kağitçibaşi, 2010; Sunar, 2002). These results indicate that the development of attachment orientations is context and experience dependent (Greenfield et al, 2003 Konrath et al, 2014 Rothbaum et al, 2000 For example, Konrath et al 2014 introduced a cohort effect in attachment orientations over a period of 20 years. Members of a generation showed similar trends in their attachment orientations, which is consistent with sociocultural practices (e.g., self‐confidence, independence, self‐sufficiency; Konrath et al, 2014 Attachment orientations, therefore, are likely to evolve as a result of biological systems and cultural adaptation (Fraley et al, 2013 Keller, 2013; Konrath et al, 2014 Rothbaum et al, 2000…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, individuals high on anxious and avoidant dimensions represent the areas of insecure attachments and are portrayed as having risk factors in coping with distress (see Mikulincer & Shaver, 2012). Some researchers regard the relationship of attachment orientations with psychological distress as universal patterns of regulating internal and interpersonal conflicts (Mikulincer & Shaver, 2012; van IJzendoorn & Sagi‐Schwartz, 2008), whereas other researchers argue that there are cultural variations in these basic patterns (Keller, 2013; Konrath, Chopik, Hsing, & O'Brien, 2014; Polek et al, 2010 Rothbaum, Weisz, Pott, Miyake, & Morelli, 2000; Wei, Liao, Ku, & Shaffer, 2011).…”
Section: Attachment Theorymentioning
confidence: 99%
“…A study of 10,000 Adult Attachment Interviews documented 35% dismissing attachment in nonclinical adolescents, as compared with only 23% of adults of the prior generation (Bakermans‐Kranenburg & van IJzendoorn, ). Konrath, Chopik, Hsing, and O'Brien (), in a study of over 25,000 American college students, reported that between 1988 and 2011, secure attachment decreased from 49 to 42% while insecure attachment increased from 51 to 58%, with the largest rise (56%) in dismissing attachments. They noted that mothers’ participation in the labor force rose from 38% in the late 1960s to 69% in the early 1990s, “straining parent's collective ability to invest quality time in their children” (p. 338), and suggested that “ changes in attachment related early childhood indicators may provide some explanation for changes in attachment styles [italics added]” (p. 338).…”
Section: Cultural Epigenetic Mechanisms Of Increased Male‐gender Psycmentioning
confidence: 99%